Development of the Arabic Grammar (Nahwu) Textbook Al-Ajurumiyyah Al-Qur'aniyyah based on the Scaffolding-Structure - Zahrotul Muzdalifah; Moh. Khasairi; Kholisin Kholisin (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
This study was conducted to meet the needs of Nahwu textbooks in Islamic boarding schools based on the scaffolding-structure based on the Al-Ajurumiyyah Al-Qur’aniyyah book by adhering to the applicable Nahwu principle. The research method used is ADDIE model development research This textbook has innovations in the form of a comprehensive concept map, the application of scaffolding theory with sentence patterns from examples of verses of the Qur’an, and a quick response code containing interesting learning content. The textbook is very valid and can be implemented after going through the validation test with the presentation of the results of material validation 95.45%, media validation 89.18%, and validation of learning 95.92%. The effectiveness test with paired t-test shows that the book being developed has a significant effect on student learning.